Efficient TM/TE Polarization Mode Tuning in p-AlGaAs/GaAsP/n-AlGaAs Diode Nanostructures by Uniaxial Compression - BOGDANOV, E. V.; KUBASHEVSKIY, E. P.; MININA, N. Ya (PHYSICS, CHEMISTRY AND APPLICATIONS OF NANOSTRUCTURES, 2015)
Numerical calculations of the optical gain of TM and TE polarization modes in strained p-AlxGa1-xAs/GaAs1-yPy/n-AlxGa1-xAs double heterostructures of different quantum well widths (from 40 to 200 Å) and phosphor contents (y = 0-0.20) were performed for different values of the external uniaxial compression along [110], [100] and [001] directions. The results of calculations demonstrate the possibility of the effective TM/TE tuning and switching by uniaxial compression along [100] and [110] directions in A3B5 zinc-blende light emitting diodes with "light hole up configuration" of quantized levels in a quantum well.